L'écran de nos pensées Stanley Cavell, la philosophie et le cinéma - Domenach, Élise (Tohu Bohu, 2021)
Great voice of the twentieth-century American philosophy, Stanley Cavell (1926-2018), heir to Wittgenstein, has devoted his life to broadening the field of philosophy to the arts in the service of a philosophy of "ordinary language". As a young philosopher, appointed professor at Harvard, he explored in a seminar of aesthetics, twenty years before Deleuze, the link between philosophy and cinema. A common thread runs throught Frank Capra to George Cukor, Terrence Malick, Arnaud Desplechin or the Dardenne brothers, amongst others: They are all underpinned by Stanley Cavell's philosophical readings of films and the films that they inspired. Few philosophical works have proved so influential in cinema and so deeply transformative in the field of film studies as that by the Harvard philosopher. From his 1971 masterpiece, The World Viewed , to his famous book on Hollywood comedy in the '40s and his later essays on melodrama, autobiography, and criticism, this book brings to light the entire breadth of Cavell's philosophy. It gives voice to three filmmakers who knew him and drew inspiration from his writing: Luc Dardenne, Arnaud Desplechin and Claire Simon. It also examines the relation between Cavell and Terrence Malick at Harvard in the '60s. This is when he laid the foundations for a philosophical approach to film that departs from our collective as well as intimate experience of films, showing how the experience unites us. For Cavell, not only do films bring us closer to each other, they also bring individuals to dive deeply into themselves and learn.